Improvement of the action of lips and embouchure in the play of brass instruments - Bārdiņš, Sandis; Marnauza, Māra (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
Embouchure, along with the activities of breathing and tongue, is one of the main components for qualitative sound creation in the playing brass instruments. In practice, there are various views about principles and methods of creating the embouchure, however, when talking about choosing the appropriate pedagogical methods, it would be important that the methods are based on the knowledge on the physics of the sound creation, as well as the anatomy of embouchure and psychophysiological processes. The article looks at the most important contradictions in this area and presents logical solutions for creating the embouchure in the pedagogical work for music school teachers and students.